Prognostic comparison of treatment methods for femoral nonunion: A retrospective study at Shahid Beheshti Hospital, Kashan, Iran - Saeed Lotfi; Seyyed Morteza Shayestehmehr; Seyed Gholamabbas Mousavi; Meisam Mazrati Hosnaroodi; Alireza Abedi (Archives of Trauma Research)
Background: In selecting the most appropriate surgical intervention, femoral nonunion remains a significant challenge for orthopedic surgeons. Previous studies have not established a definitive treatment of choice.Objectives: This retrospective cohort study evaluated the outcomes of various surgical treatments for femoral nonunion, focusing on assessing prognosis in terms of time to union and functional outcomes, as well as success rates of different surgical procedures.Methods: This retrospective cohort study, conducted from 2017 to 2022, involved a review of patient files from Shahid Beheshti Hospital in Kashan, Iran, for individuals with femoral nonunion who underwent reconstructive surgery. Patients over 18 were included, while those without follow-up, those with concomitant fractures in other femur areas, infections, open fractures, or extensive bone defects were excluded. Patient information was collected via interviews and recorded in a checklist. The primary outcome was determining the success rates of various surgical procedures used to treat femoral nonunion. This was assessed by comparing the success rates of different revision surgeries (e.g., nail exchange, refreshment and plating, dynamization) regarding radiographic union and functional recovery.Results: Forty-two patients with a mean age of 34.36 ± 15.17 years were included in the study. Surgical methods such as nail augmentation with plate, plate augmentation with plate, and nail replacement with plate achieved a 100% success rate, defined as radiographic union and clinical functional recovery. Among the methods included in the analysis, changing the nail, refreshing, and plating were effective, with no single method demonstrating superiority (OR=2.6 [0.11-62.30]). Bone grafting during the first revision surgery significantly increased the likelihood of successful union, and parathyroid hormone (PTH) administration was associated with increased success.Conclusion: These findings provide preliminary insights into the comparative effectiveness of different surgical approaches for treating femoral nonunion. They highlight the importance of considering factors such as the type of nonunion, the use of bone grafts and PTH administration in optimizing treatment strategies. Further studies with larger sample sizes are necessary to effectively compare nail exchange and plate augmentation methods.